Different colour morphs of the poison frog Andinobates bombetes (Dendrobatidae) are similarly effective visual predator deterrents. (12th March 2018) - Casas‐Cardona, Santiago; Márquez, Roberto; Vargas‐Salinas, Fernando
Abstract: Aposematism is the use of warning signals to advertise unpleasant or dangerous defences to potential predators. As the effectiveness of this strategy depends on predator learning, little variation is expected in aposematic warning signals, as similar signals facilitate predator learning. However, warning signals are frequently variable in aposematic species. Such variability could arise as a result of geographic variation in the interpretation that local predators give warning signals. We tested this divergent learning hypothesis in the polytypic poison frog Andinobates bombetes (Anura: Dendrobatidae), focusing on visual predators. Our study was conducted in two populations of this species located in the Western Andes of Colombia, where individuals at some localities exhibit red dorsolateral stripes, while those in others exhibit yellow dorsolateral stripes. We deployed paraffin models imitating both forms of A. bombetes in size and colouration, as well as dull‐coloured controls, at sites inhabited by either red‐striped or yellow‐striped frogs. Red and yellow models were attacked at similar rates at both sites, and brown models were attacked more frequently at one of the sites. These results suggest that red and yellow colourations function as similarly effective aposematic signals for primarily visual predators, regardless of the form previously experienced by these predators. Therefore, our results do not support the hypothesis of divergent predator learning as a driver of the polytypism present in this species. Finally, we discuss other mechanisms that may be involved in the evolution and maintenance of this polytypism.